2018
DOI: 10.1007/978-3-319-72682-3
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Elderly Crime and Victimization

Abstract: The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific statement, that such names are exempt from the relevant protective laws and regulations and therefore free for general use. The publisher, the authors and the editors are safe to assume that the advice and information in this book are believed to be true and accurate at the date of publication. Neither the publisher nor the authors or the editors give a w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 108 publications
0
1
0
Order By: Relevance
“…A survey study conducted with a clinical sample in Mainland China concluded that the prevalence of EFA was 13.6% [3]. Older people tend to become victims largely because they (a) are less likely to report and acknowledge being victims of financial fraud [4], (b) like keeping cash at home [5], and (c) have a higher risk of developing dementia in later life [6]. Notably, it was evident in a survey study conducted in Spain that those respondents who had been exposed to financial fraud had greater mental health needs and poorer health-related quality of life than those who had not [7].…”
Section: Introduction 1elder Financial Fraudmentioning
confidence: 99%
“…A survey study conducted with a clinical sample in Mainland China concluded that the prevalence of EFA was 13.6% [3]. Older people tend to become victims largely because they (a) are less likely to report and acknowledge being victims of financial fraud [4], (b) like keeping cash at home [5], and (c) have a higher risk of developing dementia in later life [6]. Notably, it was evident in a survey study conducted in Spain that those respondents who had been exposed to financial fraud had greater mental health needs and poorer health-related quality of life than those who had not [7].…”
Section: Introduction 1elder Financial Fraudmentioning
confidence: 99%